Synthesis of a new spirocyclic γ-lactam derivatives from 3-halogeno-3-trifluoroacetyl-1-methyl-2-pyrrolidinones - Bouillon, Jean-Philippe (Журнал органічної та фармацевтичної хімії, 2007)
3-Bromo and 3-chloro-3-trifluoroacetyl-1-methyl-2-pyrrolidinones have been obtained by the halogenation reaction of the corresponding 3-trifluoroacetyl derivatives. These compounds were fully characterized as hydrates after simple filtration on silica gel. Reactions of 3-halogeno-3-trifluoroacetyl derivatives with benzathioamide and benzamidine lead to the formation of new spirocyclic γ-lactams in moderate yields and the corresponding product of the dehalogenation of the starting substance. З-Бромо- і З-хлоро-З-трифлуороацетил-1-метил-2-піролідинони були отримані галогенуванням відповідних 3-трифлуороацетил похідних. Ці сполуки були охарактеризовані як гідрати після фільтрування через силікагель. Реакції З-галогено-З-трифлуороацетил похідних з амідом тіобензойної кислоти і бензамідином приводять до утворення з помірними виходами нових спіроциклічних γ-лактамів та відповідного продукту дегалогенування вихідної речовини. 3-Бром- и З-хлор-З-трифторацетил-1 -метил-2-пирролидиноны были получены галогенированием соответствующих 3-трифторацетил производных. Эти соединения были охарактеризованы как гидраты после фильтрования через силикагель. Реакции 3-галогено-3-трифторацетил производных с амидом тиобензойной кислоты и бензамидином приводят к образованию с умеренными выходами новых спироциклических γ-лактамов и соответствующего продукта дегалогенирования исходного вещества.